2021
DOI: 10.7150/jca.55140
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Evaluation and Clinical Prognostic Values of M6A RNA Methylation Regulators in Prostate Cancer

Abstract: Objective: M6A RNA modification is closely associated with tumor genesis and progression of several malignancies; however, its role in prostate cancer (PCa) remains poorly understood. Materials and methods: Expression data and corresponding clinicopathologic information were available freely from the Cancer Genome Atlas (TCGA) dataset. We compared the expression level of m6A RNA methylation regulators in PCa with different clinicopathologic characteristics and identified subgroups based on their expressions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Some researchers analyzed the important m6A RNA regulators, which act as prognosis factors in prostate cancer, and identified RBMX, NXF1, YTHDF1, HNRNPA2B1, and TRMT112 as critical genes that have great effects on the prognosis of PCa patients (Xu et al, 2020). Many studies have also explored expression patterns and clinical prognostic values of m6A regulators in PCa, which plays a great function in the treatment of PCa (Ou- Yang et al, 2020;Zhang et al, 2021). Nevertheless, in prostate cancer with different Gleason scores, there was still heterogeneity of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers analyzed the important m6A RNA regulators, which act as prognosis factors in prostate cancer, and identified RBMX, NXF1, YTHDF1, HNRNPA2B1, and TRMT112 as critical genes that have great effects on the prognosis of PCa patients (Xu et al, 2020). Many studies have also explored expression patterns and clinical prognostic values of m6A regulators in PCa, which plays a great function in the treatment of PCa (Ou- Yang et al, 2020;Zhang et al, 2021). Nevertheless, in prostate cancer with different Gleason scores, there was still heterogeneity of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…5 C). Researchers have studied prognosis models of PCa with modification conditions such as ferroptosis, m6A, and immune score, such as seven-gene signature discovered by Liu et al [ 25 ], eleven-gene signature discovered by Zhang et al [ 26 ], and seven-gene signature discovered by Lv et al [ 27 ]. Through comparison, we found that the accuracy of our risk signature was superior to other prognostic models according to AUC values of the ROC curve (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Risk score focuses directly on PCa cell death patterns compared to other models. Researchers have studied prognosis models of PCa with modification conditions such as ferroptosis [ 25 ], m6A [ 26 ], and immune score [ 27 ]. The higher AUC values in our model can be found by plotting the ROC curve, which means that the accuracy of our risk signature is better than other prognostic models.…”
Section: Discussionmentioning
confidence: 99%
“…The landscape of m6A variation in PCa was recently reported [ 26 , 36 40 ], although no scholars have analyzed sufficient m6A regulators and verified them using clinical PCa tissues. To overcome these shortcomings, we explored all 25 widely-acknowledged m6A regulators and assessed relevant associations of various clinicopathological characteristics, such as TN, GS, pT, TP53 mutation, and survival analysis of RFS using TCGA-PRAD data.…”
Section: Discussionmentioning
confidence: 99%